Aeon Anggun Rawang, Rawang,Selangor Darul Ehsan / Ahmad Mu’az Ahmad ... [et al.] - Ahmad, Ahmad Mu’az; Abu Bakar, Azlan; Abdul Razak, Muhammad Zariff; Mohd Rosley, Fahda Amani; Sharom, Nurfazirah (Universiti Teknologi Mara, Perak, 2016)
This report represent the building of the Aeon Anggun Mall Rawang as for the case study for Integrated Final Project (BSR ).subject. From the first day of the visiting, it is to find the building and take the full permission to do the study work from department facilities management of Aeon Anggun Rawang’s. There are tons of information that have to find and collect through a few ways regarding to the several chapters such as building background, building design, building services, maintenance management, legal aspect, and maintenance financial budget. The method to get the information is by general research, observation, took some photos as the evidence, interview session and from lecturer notes. The building have two main floor which the ground floor and 1st floor is full with various of tenant such as Old Town White Coffee, Big Apple, Penang xpress. AEON Anggun Mall Rawang using two maintenance department which are in house and also out source. Moreover, every service is run by special skill work. Maintenance strategy was performed to observe and managed the function of the building to be in good condition, safe and comfortable for the occupants and system in the building. AEON Anggun Rawang has 104 tenant that has been agree with the requirement that been list by the AEON Department.The contract content for the tenant and maintenance must follow the contract , if any problem happened AEON Anggun Rawang can take an action on ending the contract for example the tenant not paying the rent. Next is the regulation of AEON Anggun Rawang comply with the Uniform Building By Law 1994 (UBBL 1984), Street Drainage & Building 1974 (ACT 1974), Occupational Safety & Health 1994 (OSHA) and Electricity Supply Act 1990 (Act 447). As for the cash flow, the income of AEON Anggun Rawang gained from the allocation maintenance, tenant rental, kiosks, weighing scale machine, parking lot and massage chair. The expenditure is on the maintenance outsource, utilities, general expenditure such as office expenditures, staff salaries and network bills.